Kinetic Study of the Metal Ions Doped TiO2 Samples for the Photocatalytic Degradation of E 131 VF - Estephane,C. (2020)
The present work is focused on the influence of the metal salts on the photocatalytic efficiency of TiO2 for the elimination of E 131 VF food colorant. Two series of TiO2 photocatalysts loaded with Fe(II) and Cu(II) were prepared by using the wet impregnation method. The samples were characterized by XRD, IR, Raman and scanning electron microscopy. The degradation of the food colorant was followed by the measurement of the absorbance. The kinetics of degradation fitted well to the zero pseudo order with Cu-TiO2, but it followed the 1st order with Fe-TiO2. In general, the photoactivity of TiO2 was reduced by the presence of the transition metal ions, even at low molar ratio %. The recalcination of the doped samples at higher temperatures reduced more the degradation activity. Several reasons were suggested to explain the dramatic decrease in the activity of the prepared samples.